2002
DOI: 10.1111/1475-679x.t01-1-00056
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Affective Reactions on Risky Decision Making in Accounting Contexts

Abstract: In this study we examine whether managers’ affective reactions influence their risk–taking tendencies in capital budgeting decisions. Prior research on risky decision making indicates that decision makers are often risk averse when choosing among alternatives that yield potential gains, and risk taking when the alternatives yield losses. The results reported here indicate that negative or positive affective reactions can change this commonly found risky behavior. Managers were generally risk avoiding (taking) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 32 publications
3
99
1
1
Order By: Relevance
“…They find that managers tending to reject investment alternatives that elicit negative emotional responses and accept another investment alternative that elicit neutral emotional responses, even though the rejected alternatives have higher economic values. Moreno, Kida and Smith (2002) extends Kida et al (2001) to test the impact of affective reactions on risky decision making in accounting context; they also found that affect reactions can change managers' risky behavior: when affect was present, they tended to reject investment alternatives that elicited negative affect and accept alternatives that elicited positive affect, resulting in risk taking (avoiding) in gain (loss) contexts. Individualism is one of Hosftede five culture dimensions, which refers to the degree of people choose their own interests or alternatively take responsibility to act as a member of a group.…”
Section: The Role Of Affect In Judgment and Decisionsupporting
confidence: 54%
See 1 more Smart Citation
“…They find that managers tending to reject investment alternatives that elicit negative emotional responses and accept another investment alternative that elicit neutral emotional responses, even though the rejected alternatives have higher economic values. Moreno, Kida and Smith (2002) extends Kida et al (2001) to test the impact of affective reactions on risky decision making in accounting context; they also found that affect reactions can change managers' risky behavior: when affect was present, they tended to reject investment alternatives that elicited negative affect and accept alternatives that elicited positive affect, resulting in risk taking (avoiding) in gain (loss) contexts. Individualism is one of Hosftede five culture dimensions, which refers to the degree of people choose their own interests or alternatively take responsibility to act as a member of a group.…”
Section: The Role Of Affect In Judgment and Decisionsupporting
confidence: 54%
“…Kida, Moreno and Smith (2001) find that these affective reactions especially negative affect will influence managers' capital-budgeting decisions; managers will reject alternative that elicit negative affect even though it has higher economic values. Kida and Smith (2002) provide evidence that affective reaction will influence managers' risk-taking tendency in capital budget-making. Generally, according to prospect theory, managers are risk-avoiding for gains and risk-taking for losses in the absence of affective reaction.…”
Section: Introductionmentioning
confidence: 94%
“…Both perceived damage and shopping alternatives showed strong and consistent impacts across two datasets and explained 24-38% of the variance in retreative behaviors, together with control variables. This moderate explanatory power suggests that information security research in the B2C e-commerce area may need to consider irrationality in online customers' decision making processes and potential effects of affective reactions (e.g., emotion) (Moreno et al 2002;Yang and Lester 2008). Our data also suggests that increases in phishing and spam messages have a very strong positive effect on the perception of damage, followed by the time and effort that the affected customers had to spend in order to prevent potential information security problems.…”
Section: Conclusion and Discussionmentioning
confidence: 76%
“…Kahn & Isen, 1993;Mano, 1990;see Ashby et al, 1999, for a review). Interpersonal emotional reactions have been found to influence performance appraisals (Robbins & DeNisi, 1994;Tsui & Barry, 1986;Varma et al, 1996), risky decision making (Moreno, Kida, & Smith, 2002), and negotiation performance (Allred, Mallozzi, Fusako, & Raia, 1997;O'Connor & Arnold, 2001;Pillutla & Murnighan, 1996).…”
Section: Affective Reactionsmentioning
confidence: 99%